The Influence of Cu-Additions on the Microstructure, Mechanical and Magnetic Properties of MnAl-C Alloys - Juerries, Florian; Freudenberger, Jens; Nielsch, Kornelius; Woodcock, Thomas George (Scientific Reports, 2020)
Alloys of the form (Mn54Al44C2)100-xCux (with x = 0, 1, 2, 4 and 6) were produced by induction melting. After homogenisation and quenching, most of the alloys consist entirely of the retained ε-phase, except for x = 6, in which the κ-phase was additionally present. After subsequent annealing, the alloys with x ≤ 2 consist entirely of a Cu-doped, ferromagnetic τ-phase, whereas the alloys with x > 2 additionally contain the κ-phase. The polarisation of the alloys at an applied field of 14 T decreases with increasing Cu-content, which is attributed i) to the dilution of the magnetic moment of the τ-phase unit cell by the Cu atoms, which do not carry a magnetic moment, and ii) at higher Cu-contents, to the formation of the κ-phase, which has a much lower polarisation than the τ-phase and therefore dilutes the net polarisation of the alloys. The Curie temperature was not affected by the Cu-additions. The stress needed to die-upset the alloys with x ≤ 2 was similar to that of the undoped alloy, whereas it was much lower for x = 4 and 6, due to the presence of intergranular layers of the κ-phase. The extrinsic magnetic properties of alloys with x ≤ 2 were improved by die-upsetting, whereas decomposition of the τ-phase during processing had a deleterious effect on the magnetic properties for higher Cu-additions.
CRIS-Team Scopus Importer:2022-04-14